Submerged plant planting machine - SONG XUAN; WU MEILING; ZOU HONGJU; CHAI XIA; LIU PINGPING (2015)
The invention discloses a submerged plant planting machine. The submerged plant planting machine comprises a first bearing frame arranged on a ship, and a control console, a plant placing device and a second bearing frame which are arranged on the first bearing frame as well as a plurality of planting poles and a gear, wherein a plurality of motors and gears, which are controlled by the control console are arranged on the second bearing frame side by side, the gears are arranged side by side and are respectively connected with a fixed bearing, and the fixed bearing is used for connecting each motor with the corresponding gear in a transmission manner by virtue of a transmission chain; and the planting poles are vertically arranged on the first bearing frame side by side and are inserted into water surface, a plurality of rectangular openings meshed with the gears are formed in one side, dead against the gears, of each planting pole, and the motors drive the gears to operate and further drive each planting pole to move up and down. The submerged plant planting machine has the advantages that the submerged plant planting efficiency can be improved, the planting density can be standardized, the influence of severe weathers on planting conditions is alleviated, labour force input and usage amount are reduced, and further every cost for submerged plant planting is reduced, so that the submerged plant planting machine has a broad market prospect.